Agricultural Mechanisation in the Hills of Uttarakhand - Agrawal, Abha; Manral, Laxmi (Archives of Business Research, 2022)
Agricultural Mechanisation in India has completely changed the condition and direction of agriculture. After mechanisation India has emerged as one of the biggest producer of food grains and also net exporter. But the development of mechanisation has been very uneven some states like Punjab, Haryana and Uttar Pradesh are highly mechanized while the hilly states like Uttarakhand still struggling with traditional methods of farming. Farmers in Uttarakhand especially in hilly regions are still using outdated and old methods of farming which are not feasible with this modern and technically advance world where there is high demand of food grains due to increasing population. People are still doing subsistence farming manually which has made it drudgery prone occupation. Agricultural mechanisation will make agriculture less drudgery and more efficient for the farmers. It helps in increasing farm productivity and production. This paper highlights the existence of agricultural mechanisation in hilly regions and the issues faced in transformation of agriculture.